(untitled) (Bangladesh Journal of Medicine, 2026)
Background: The rising incidence of Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) in young adults (aged 18-45 years) represents a critical and underappreciated public health challenge. This meta-analysis aims to quantify the global prevalence of MASLD in this demographic and evaluate its association with accelerated progression to advanced liver disease. Methods: A systematic literature search was conducted across PubMed, Scopus, and the Cochrane Library for studies published between January 2015 and October 2025. Observational studies reporting incidence, prevalence, or longitudinal outcomes of MASLD in young adults were included. Pooled prevalence and hazard ratios (HRs) for clinical outcomes were calculated using a random-effects model. Results: Analysis of 24 studies (n>1,450,000 participants) revealed a pooled global prevalence of MASLD in young adults of 25.5% (95% CI: 21.3–30.4%). Significant geographical heterogeneity was observed, with the highest prevalence in the Middle East (33.5%) and North America (31.2%). Compared to late-onset MASLD (diagnosis >55 years), young adults exhibited a significantly faster fibrosis progression rate (HR 1.45), a higher risk of cirrhosis by age 60 (HR 3.20), and an increased risk of cardiovascular events (HR 1.85). An estimated 10-20% of young adults with MASLD develop moderateto- advanced fibrosis (e”F2) within a decade of diagnosis. Conclusion: MASLD in young adulthood is a highly prevalent and aggressive phenotype, portending a substantial future burden of end-stage liver disease. The “silent” nature of early disease progression underscores the urgent need for targeted screening and early intervention strategies in this population to mitigate a looming epidemic of advanced liver complications. Bangladesh J Medicine 2026; 37(1): 10-14